Mating modifies the expression of crucial oxidative-reductive transcripts in the pig oviductal sperm reservoir: is the female ensuring sperm survival? - Álvarez-Rodríguez, Manuel; Roca, Jordi; Martínez, Emilio A.; Rodríguez-Martínez, Heriberto (Frontiers in Endocrinology, 2023)
Background: Mating induces large changes in the female genital tract, warranting female homeostasis and immune preparation for pregnancy, including among its pathways the preservation of crucial oxidative status. Being highly susceptible to oxidative stress, sperm survival and preserved function depend on the seminal plasma, protection which is removed during sperm handling but also after mating, when spermatozoa enter the oviduct. Therefore, it is pertinent to consider that the female sperm reservoir takes up this protection, providing a suitable environment for sperm viability. Since these aspects have not been explored despite the increasing strategies in modulating the female status through diet control and nutritional supplementation. Aims: To test the hypothesis that mating modifies the expression of crucial oxidative-reductive transcripts across the entire pig female genital tract (cervix to infundibulum) and, particularly in the sperm reservoir at the utero-tubal junction, before ovulation, a period dominated by oestrogen stimulation, of ovarian as well as of seminal origin. Methods: The differential expression of oestrogen (ER) and progesterone (PR) receptors and of 60 oxidative-reductive transcripts was studied using a species-specific microarray platform, in specific segments of the peri-ovulatory sow reproductive tract in response to mating. Results: Mating induced changes along the entire tract, with a conspicuous down regulation of both ER and PR and an upregulation of superoxide dismutase 1 (SOD1), glutaredoxin (GLRX3), peroxiredoxin 1 and 3 (PRDX1, PRDX3), among other NADH Dehydrogenase Ubiquinone Flavoproteins, in the distal uterus segment, perhaps preventing oxidative stress in the area adjacent to the in the sperm reservoir at the utero-tubal junction. Concomitantly, there was a downregulation of catalase (CAT) and NADH dehydrogenase (ubiquinone) oxidoreductases 1 beta subcomplex, subunit 1 (NDUFB1) in the utero-tubal junction alongside an overall downregulation of CAT, SOD1, and PRDX3 in the ampullar and infundibulum segments. Conclusions: Natural mating i is an inducer of changes in the expression of female genes commanding antioxidant enzymes relevant for sperm survival during sperm transport, under predominant oestrogen influence through blood stream and semen. The findings could contribute to the design of new therapeutics for the female to improve oxidative-reductive balance.